1994
DOI: 10.1002/j.1460-2075.1994.tb06822.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dynamics in an immortal human cell line.

Abstract: The integration of transfected plasmid DNA at the telomere of chromosome 13 in an immortalized simian virus 40‐transformed human cell line provided the first opportunity to study polymorphism in the number of telomeric repeat sequences on the end of a single chromosome. Three subclones of this cell line were selected for analysis: one with a long telomere on chromosome 13, one with a short telomere, and one with such extreme polymorphism that no distinct band was discernible. Further subcloning demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
245
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(261 citation statements)
references
References 42 publications
13
245
0
3
Order By: Relevance
“…Cleavage of long telomeres to wild type size may occur within a single cell division (Li and Lustig, 1996). Further, tagged telomeres in telomerase-negative immortal human cells were occasionally found to undergo rapid shortening and subsequent rapid relengthening, indicating that telomerase activity is not essential for rapid telomere shortening (Murnane et al, 1994). The telomere loss evidenced in our GM8476HFF5 hybrids suggests that ALT is also not required for rapid shortening as presumably it has already been repressed.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Cleavage of long telomeres to wild type size may occur within a single cell division (Li and Lustig, 1996). Further, tagged telomeres in telomerase-negative immortal human cells were occasionally found to undergo rapid shortening and subsequent rapid relengthening, indicating that telomerase activity is not essential for rapid telomere shortening (Murnane et al, 1994). The telomere loss evidenced in our GM8476HFF5 hybrids suggests that ALT is also not required for rapid shortening as presumably it has already been repressed.…”
Section: Discussionmentioning
confidence: 74%
“…Some immortalized cell lines, however, do not have any detectable telomerase activity but have a highly characteristic pattern of telomere lengths that range from very short to abnormally long (Murnane et al, 1994;Bryan et al, 1995. This pattern of heterogeneous telomere lengths is maintained over many hundreds of population doublings (Rogan et al, 1995), indicating that telomere maintenance can occur in the absence of detectable telomerase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Most cancers utilize telomerase (Greider and Blackburn, 1985) for this purpose, but a significant minority utilize an alternative lengthening of telomeres (ALT) mechanism (Bryan et al, , 1997. Although details of the molecular mechanism of ALT are largely unknown, previous studies have shown that ALT in human cells involves telomere-telomere recombination (Murnane et al, 1994;Dunham et al, 2000). With a few exceptions (Cerone et al, 2005;Fasching et al, 2005;Marciniak et al, 2005;Brachner et al, 2006), the hallmarks of human ALT cells include (1) a unique pattern of telomere length heterogeneity, with telomeres that range from very short to greater than 50 kb long and (2) the presence of ALT-associated promyelocytic leukemia (PML) nuclear bodies (APBs) containing (TTAGGG)n DNA and telomere-specific binding proteins (Yeager et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres are also important in the maintenance of chromosomal stability (Counter et al, 1992;Murnane et al, 1994). In cells that bypass the normal cellular senescence pathway (Shay et al, 1991b), the reactivation of telomerase occurs when the telomeres have reached a critically shortened length (Harley et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no reports of telomerasenegative tumor-derived cell lines with short telomeres (58 kb) (Avilion et al, 1996;Harley et al, 1994;Shay and Bacchetti, 1997). However, several examples of experimentally immortalized cultured cell lines have been reported that proliferate inde®nitely with long, heterogenous telomere lengths, without the presence of detectable telomerase activity Duncan et al, 1993;Murnane et al, 1994;Wright et al, 1989;Wright and Shay, 1992).…”
Section: Introductionmentioning
confidence: 99%